2016
DOI: 10.5114/wo.2016.65606
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum level of HE4 and CA125 considering selected risk factors among patients with endometrioid endometrial cancer

Abstract: The aim of the studyTo assess the difference of serum level of HE4 and CA125 among patients with endometrioid endometrial cancer, considering the presence or absence of selected risk factors.Material and methodsA retrospective study of 46 patients, whose serum level of HE4 and CA125 level was documented, admitted to our Clinic because of endometrioid endometrial cancer. The statistical difference of both markers was analyzed considering certain risk factors.ResultsIn the examined group of patients there was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It is postulated that HE4 is better than CA125 in diagnosing patients with EOC due to high specificity. However, HE4 increases with age, smoking and renal diseases 9 . There are several methods to estimate serum CA125 and serum HE4, such as Enzyme-linked immunosorbent assay (ELISA), Radioimmunoassay (RIA), Chemiluminiscence immunoassay (CLIA) and Electrochemiluminesce immunoassay (ECLIA).…”
Section: Introductionmentioning
confidence: 99%
“…It is postulated that HE4 is better than CA125 in diagnosing patients with EOC due to high specificity. However, HE4 increases with age, smoking and renal diseases 9 . There are several methods to estimate serum CA125 and serum HE4, such as Enzyme-linked immunosorbent assay (ELISA), Radioimmunoassay (RIA), Chemiluminiscence immunoassay (CLIA) and Electrochemiluminesce immunoassay (ECLIA).…”
Section: Introductionmentioning
confidence: 99%
“…The same authors also reported higher HE4 protein levels in women with atypical hypertrophy of endometrium in comparison to healthy women with normal endometrium [11]. There is a similar study concerning the clinical stage, the degree of differentiation and prognosis conducted by a Polish team, which leads to the same conclusions [12]. This may be of great clinical importance, as the initial histologic grade and the tumor size have an impact on overall survival in endometrial cancer [13].…”
Section: Discussionmentioning
confidence: 73%
“…It was observed that HE4 expression levels in malignant tissues are positively correlated with tumor sizes and stages, invasion and metastasis, and negatively correlated with patient survival, in ovarian as well as endometrial cancers [31][32][33]. In pancreatic cancers, higher HE4 expression levels in tumor tissues are closely correlated with larger tumor sizes and more advanced stages of malignancies [24].…”
Section: Discussionmentioning
confidence: 99%